DOUBLE-ROTOR FLUX-SWITCHING MACHINE (2013)
Advantageous machines, such as flux-switching machines (FSMs) are provided. An FSM can be yokeless and can have two rotors, which can be displaced from one another (e.g., by half a pole pitch). An FSM can be a flux-switching permanent magnet machine (FSPMM), and all magnets can be magnetized in the same circumferential direction. FSMs of the subject invention are cost-effective, have high torque density, and can operate well even under fault conditions.